1969
DOI: 10.3109/13682826909011481
|View full text |Cite
|
Sign up to set email alerts
|

The Rationale for a Temporary Speech Prosthesis in Palatal Insufficiency

Abstract: FOR the speech clinician who is experienced in the evaluation of children with repaired cleft palate it is not difficult to determine that a child's palate is inappropriate in movement and/or length for adequate voice and articulation development. A child evaluated at two, two-and-a-half, and three years of age will generally have given enough speech clues for the clinician to make such a judgement. No x-ray studies need be required to make this determination, only the trained ear of the clinician and his obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

1972
1972
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 4 publications
0
6
0
2
Order By: Relevance
“…16 The overall findings of the investigations indicated that the elimination of compensatory errors had a positive influence on velopharyngeal movement, 21 but hypernasality and nasal emission remained to some degree. 10 At about the same time studies were conducted by several investigators [22][23][24][25][26] who evaluated the use of speech appliances to reduce hypernasality. Clients were fitted with speech appliances constructed by a prosthodontist.…”
Section: History Of Behavioral Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The overall findings of the investigations indicated that the elimination of compensatory errors had a positive influence on velopharyngeal movement, 21 but hypernasality and nasal emission remained to some degree. 10 At about the same time studies were conducted by several investigators [22][23][24][25][26] who evaluated the use of speech appliances to reduce hypernasality. Clients were fitted with speech appliances constructed by a prosthodontist.…”
Section: History Of Behavioral Treatmentmentioning
confidence: 99%
“…After a period of use, the appliances were gradually reduced in size. Some reports indicated that clients were able to eliminate wearing the appliance and maintain closure for speech; 22,26 other studies did not. 25,[27][28][29][30] Additional studies have been performed to examine other sensory treatments such as electrical stimulation and touch pressure stimulation.…”
Section: History Of Behavioral Treatmentmentioning
confidence: 99%
“…There is little data reported to recommend the use of speechbulb reduction programs or the temporary use of prosthetic appliances. Blakely (1969) and Weiss (197 1) reported series of patients who had undergone speech-bulb reduction. Variability of articulation skills was not taken into account in these studies as a factor influencing success.…”
Section: Frequency O F Correct Responsementioning
confidence: 99%
“…O procedimento para a indicação e a confecção da prótese, em particular, é complexo e requer a atuação transdisciplinar entre a odontologia, a fonoaudiologia e também a cirurgia plástica (WOOD; WATERTOW, 1950;HARKINS, 1951;MCDONALD, 1951;HARKINS, 1960;SHELTON;LLOYD, 1963;BZOCH, 1964;CURTIS;CHIERICI, 1964;MAZAHERI, 1964;BLAKELEY, 1964;ALLEY, 1965;GORBAN;DIAZ, 1966;BLAKELEY, 1969;WONG;WEISS, 1972;DALSTON, 1977;ROGERS, 1980 O uso do obturador para estimular os movimentos das paredes faríngeas foi discutido por vários autores que, de uma forma geral, sugerem que a presença de um obturador na faringe pode afetar o padrão da atividade velofaríngea (BERRY et al,1983;WALTER, 1990;ANDERSON, 1990;ISRAEL;BLAKELEY, 1993;TACHIMURA et al, 2000a;TACHIMURA et al, 2000b;PETERZON-FALZONE et al, 2001;WILLIAM et al, 2004;PEGORARO-KROOK et al, 2004;PETERSON-FALZONE, 2006;DUTKA et al, 2006). Apesar de os autores mencionados não discordarem quanto ao fato de o bulbo faríngeo ter o potencial de alterar a atividade muscular do mecanismo velofaríngeo, estudos comparativos do funcionamento desse mecanismo antes e após o uso do obturador faríngeo são limitados.…”
Section: Discussionunclassified
“…Segundo os autores, desde que corretamente indicada, a prótese pode constituir um complemento da cirurgia. Blakeley (1969) sugeriu um plano de tratamento precoce para crianças de três a quatro anos com insuficiência velofaríngea, com obturador faríngeo. De acordo com o autor, a criança deveria usar a prótese constantemente e, à medida que a voz e a articulação fossem se desenvolvendo, o bulbo teria o seu tamanho reduzido.…”
Section: Mazaheri (1964) Estabeleceu As Indicações E Contra-indicaçõeunclassified